The Source Mechanism and Fault Movement Characterization of the 2022 Mw6.7 Menyuan Earthquake Revealed by the Joint Inversion With InSAR and Teleseismic Observations - Bao, Xin; Zhang, Rui; Wang, Ting; Shama, Age; Zhan, RunQing; Lv, Jichao; Wu, Renzhe; Fu, Yin; Liu, Guoxiang (Frontiers in Environmental Science, 2022)
The characteristics of active fault movements are essential for estimating the earthquake potential on the Tibetan Plateau (TP) in a complex geological setting. The 2022 Menyuan Mw6.7 earthquake was studied by a joint seismological and geodetic methodology to deepen the scientific understanding of the source parameters and deformation mechanisms. Firstly, the entire InSAR co-seismic deformation field is obtained based on ascending and descending Sentinel-1A imagery. Subsequently, a Bayesian algorithm is applied in fault geometry and slip distribution determination by combining InSAR measurements and teleseismic data. And the fault movement characteristics of the 2022 Menyuan earthquake are analyzed. Finally, a comprehensive "surface-subsurface" analysis of the effects caused by this earthquake was carried out by combining InSAR and fault data. The results demonstrate that the ground settlement and uplift induced by the 2022 Menyuan earthquake are significant, with a maximum relative deformation of 56 cm. The seismogenic fault is on the junction of the Lenglongling (LLL) and Tuolaishan (TLS) faults, and the main body is in the western part of the LLL fault, a high dip left-lateral strike-slip fault with NWW-SEE strike. The slip distribution results indicate that the largest slip of 3.45 m occurs at about 5 km below the ground, and the earthquake magnitude is Mw6.63. And further analysis by integrated geological structure and inversion results reveals that the earthquakes that occurred on the North Lenglongling Fault (NLLL) in 1986 and 2016 have contributed to the 2022 Menyuan earthquake.